PEMBERDAYAAN MASYARAKAT TERDAMPAK ERUPSI MERAPI MELALUI PEMBUATAN PERANGKAT PEMBELAJARAN INOVATIF BERBAHAN DASAR LIMBAH ANORGANIK DAN IMPLEMENTASINYA SEBAGAI MEDIA TRAUMA HEALING DALAM PEMBELAJARAN SAINS - Suyoso, -; Purwanto, Budi; Widodo, Eko (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2016)
Community empowerment through students' community service aimsto improve the community skill in producing science props from inorganicwaste materials by mentoring method as Trauma Healing media in sciencelearning. The subject of this community service was Kepuharjo, Cangkringanvillagers. The implementation of thiscommunity service was devided into fourstages ie; first university students designing and creating science props, secondthe designing and creating science props workshop for the community, thirdcreating science props by community with students mentoring, fourth displaying the science props that has been produced by the community. The display was held in two schools namely SMP Negeri 2 Cangkringan and SD Negeri Kepuharjo. The result shows thatthe community is able to create science props. Eight science props unitshad been tested in those schools. Based on students and teachers responses to the science props, they were satisfied. It is indicated that the science props made by community and used as Trauma Healing media in learning science were effective